How Individual Characteristics Affect Ethical Decision Making - Kasingku, Frisky Jeremy (Wahana Riset Akuntansi, 2023)
Purpose – The purpose of this research is to empirically examine the impact of individual characteristics toward ethical decision making.Design/methodology/approach – Causal descriptive method is used in this study with primary data sources. Individual characteristics are measured by using idealism, relativism, Machiavellianism, locus of control, deontology, consequential, and risk orientation. On the other hand, ethical decision making is measured by using the intention to commit white-collar crime. The purposive sampling method was used to select the sample for this study. Furthermore, an online questionnaire was administered to collect the data. The questionnaire was distributed to 166 accounting and management students as samples for this study.Findings – The statistical results showed that there is a significant influence of idealism, relativism, Machiavellianism, and partially significant influence of deontology on actions to commit white collar crime.Originality/value – This study uses another personality test other than big-five personality and linked it to the white-collar crime case.Research limitations/implications – This study may contribute to the management of the company when they design the control system within the company.